Implementasi Metode Project Oriented Problem Based Learning (POPBL) Untuk Meningkatkan Hasil Belajar Fiqih Siswa Kelas VIII MTs Nurbahri Bubun Kecamatan Tanjung Pura - Muhammad Saleh, Ahmad Zaki, Mila Raihan, (CV. PUSDIKRA MITRA JAYA, 2023)
From the results of the research that has been done, it shows that the project oriented problem based learning method is significantly better in improving student learning outcomes. Efforts to improve student learning outcomes for class VIII MTs Swasta Nurbahri Bubun in the subjects of Jurisprudence on the material of prostration, gratitude and recitations were carried out by applying the Project oriented problem based learning learning strategy with two cycles and showed an increase in student learning outcomes. The application of learning strategies Project oriented problem based learning is carried out in Jurisprudence lessons in class VIII MTs Swasta Nurbahri Bubun by implementing according to the plans that have been made, learning activities are carried out by starting with giving pretests to students, then forming study groups by dividing the material in each group. . The next step is still in the teacher's guidance in the form of class percentage actions and group work carried out by students and ends with giving conclusions and post tests. Efforts to improve student learning outcomes for class VIII MTs Swasta Nurbahri Bubun in the subjects of Jurisprudence on the material of prostration, gratitude and recitation after the application of the Project oriented problem based learning learning method in the first cycle the average value increased to 85 with the percentage of completeness of 77% and the percentage of completeness learning has not reached 85%. And the second cycle the average value of students reached 94 (30 students) with a 100% completeness percentage with an increase in the difference from cycle I to cycle II of 41%. Thus the second cycle experienced a significant increase, so the researchers concluded that there was no need to continue again in the next cycle.